FUNDAMENTALS OF EFFECTIVE MENTORSHIP how to develop intellectual capacity and healthy... workplace culture. - Aslett, Matthew ([S.l.] : PRODUCTIVITY PRESS, 2025)
This book communicates critical considerations for the delivery of mentorship programs and the creation of mentorship relationships. Readers are introduced to the mentorship styles and learn about why mentorship must be prioritized in their organizations.
4. Outcomes for Mentees, Mentors, and Communities -- Consequence Types in Mentorship Programs -- Multilevel Perspectives in Mentorship Environments -- Mentorship Program Benefits -- Mentorship Program Drawbacks -- Mitigation Plans for Mentorship Program Challenges -- Mentorship Program Mediators and Moderators -- Consolidation of Outcomes for Mentors, Mentees, and Communities -- 5. Mentorship Styles and Philosophies -- Individualized Mentorship Philosophy -- Philosophical Reflection Areas -- Philosophical Manifestation into Mentorship Styles -- Framing Appropriate Styles through Objectives
Keywords: Mentoring